Firm Size Sebagai Salah Satu Penentu Audit Delay - Muhammad Saifi; Kemal Sandi; Lusi Kurnia (Journal of Economic, Bussines and Accounting (COSTING), 2024)
This article examines the contribution of company size as a determinant of Audit Delay for Property and Real Estate Companies listed on the Indonesia Stock Exchange in 2018-2022. The novelty of the research is to develop a new model related to the determinants of Audit Delay, especially the company size variable. Another novelty in this study is that it is more comprehensive in seeing the effect of Profitability and Leverage on Audit Delay and company size as a mediating variable. The number of samples is 26 companies with a period of 5 years, 2018-2022. Research hypothesis testing using Structural Equation Model (SEM) based on Partial Least Square (PLS). The results showed that Profitability has a significant negative effect on Audit Delay, Leverage has a significant positive effect on Firm Size, Leverage has a significant negative effect on Audit Delay, Firm Size has a significant negative effect on Audit Delay, Profitability has an insignificant effect on Firm Size, Leverage has a significant negative effect on Audit Delay through Firm Size, and Profitability has an insignificant effect on Firm Size through Firm Size. Keywords: Firm Size, Audit Delay